P54 A service review of fibroscan at King's College Hospital, opportunities for service improvement in non-hepatology specialities. (20th September 2022) - Han, Khin; Adibe, Ngozi; Ajaz, Saima; Mohamed, Almuthana; Guerra-Veloz, Maria; Lok, James; Carey, Ivana; Agarwal, Kosh
Abstract : Background and Aims: Fibroscan is a non-invasive test widely used in diagnosing, managing, and prognosis of chronic liver diseases of various etiologies. It is user-friendly but less applicable when compared with serum biomarkers in ascites, obesity and operator experience cases. In addition, it is not available outside the secondary and tertiary care. The study aims to perform a service review of the impact on fibroscan access during covid pandemic and to explore the opportunities to improve the service. Method: Analysis of retrospective data at King's College Hospital in 2021 and compared the first six months' data to that of 2019 (pre-covid period). Data including indications, types of referral, fibroscan interval, results and fasting state of the patients were collected using electronic patient records. Results: A total of 2509 patients had fibroscan performed in 2021 and 1038 patients (41%) were viral hepatitis, followed by NAFLD/NASH(n=583) and autoimmune hepatitis/primary biliary cirrhosis/primary sclerosing cholangitis (299). The remaining 72 cases were referred from different specialities (dermatology and rheumatology). Two hundred forty-four cases (12%) were referred externally from district hospitals and other specialities. Among the external referrals, 174 out of 187 (77%) liver-related cases were referred from Princess Royal University Hospital. Apart from 1109 cases done as the first scan, 926 cases (66%) were repeated within three years, 351 (25%) for more than three years and 126 (9%) within one year. Only 25 to 30% had LSM (liver stiffness measurement) differences by ≥3kPa (20%) in all three intervals. 282 patients (11%) have liver stiffness measurement (LSM) of more than 12.5kPa. The mean LSM value of hepatitis patients were 6.3kPa and those of NAFLD/NASH patients was 9.4kPa. Only two cases were documented for being unfasted prior to the scan and the remaining cases were unknown. Conclusion: Unsurprisingly, there were 1.5 times more fibroscan cases in the pre-covid year (1633 in 2019 compared to 1058 in 2021), indicating the negative impact of COVID-19 in the diagnosis of chronic liver diseases. In addition, NAFLD had a higher rate of advanced fibrosis compared to hepatitis B with the possibility of more sequential HBV follow-up, late referral of NAFLD or impact of fasting state on steatohepatitis. We need to evaluate the interval and indications of repeat fibroscan in each etiology due to no significant variation of LSM value despite different fibroscan intervals. We also need to improve the fibroscan access in district hospitals and other specialities regarding external referral data.